Organização partidária e coordenação eleitoral no Brasil - Souza, Fabiana Cristina dos Santos de (Universidade Federal de São Carlos, 2020)
Faced with the importance of parties for the consummation of democratic regimes, some issues emerge in relation to their functioning, mainly related to how decisions are made within the consortia. Thus, the central objective of this research is to analyze the political parties through their internal organization, since, as Panebianco (2005) points out, the parties must, first, be understood as organizations that vow to occupy the government and the legislative. The key question that permeates the analysis is how party strategy, nationalization or provincialization, whether pure or national, focuses on the chances of a party launching nominations for governors and senators in national elections, as well as sewing agreements elections? The intention is to understand how the parties outline their electoral strategies according to the autonomy or centralization granted to subnational bodies. The proposed cut includes the six main Brazilian parties: PT, PSDB, PMDB, PSB and DEM, analyzing the elections that took place in 2010, 2014 and 2018 for governors and federal deputies of the 27 Brazilian states. The hypothesis is that the launch of presidential candidacies corroborates the adoption of a presidential strategy, causing the national summit to centralize the process of launching candidatures for Governor and Senator, seeking support at the national level. Thus, parties directly involved in the PT and PSDB presidential elections together with the DEM, which traditionally is a source of support for the latter, and the traditional PT partner PSB would impose further restrictions on the state summit by establishing certain options for partisan coalitions in the states as well as in the launching of applications, in view of the national scenario. The PMDB seeks through the state elections to nationalize their votes, which incurs greater autonomy at the state levels of the party. To test the hypothesis will be observed the electoral resolutions of the parties, which dictate the main guidelines that guide them in the national elections.
Party organization and electoral coordination in Brazil
Keywords: Partidos políticos; Seleção de candidatos; Coordenação; Political parties; Selection of candidates; Coordination; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO